PENYELARASAN KURIKULUM PRODI PTM FKIP UNS KONSENTRASI OTOMOTIF DENGAN DUNIA INDUSTRI - Yogi Alifudin Pradana; Ranto Ranto; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The speed of the times in terms of technology and people's behavior patterns makes people around the world interconnected. This makes the competition for jobs in society increase. Everyone who wants to survive the competition for a job must have the ability and skills. In this case, the world of education is also influential, where education is not only to seek knowledge but to find or improve skills that are useful for competing for a job. In technological advances, especially in the automotive sector, the world of education, especially vocational education, must always follow the development of technology in the industry. The PTM Study Program should have a curriculum that is in line with the work or competencies in the industry so that ptm study program graduates can compete in the world of work. This study aims to find out whether the curriculum of the PTM FKIP UNS study program has aligned with the competencies needed by the industrial world. This research is a qualitative descriptive research. The source of this research data is documents from industry and the Mechanical Engineering Education Study Program. Purpose sampling data retrieval technique. Data collection was carried out with documentation and finalized with FGD (Focus Group Discussion). There are three data collection points, namely Toyota Nasmoco Ringroad, Daihatsu Adi Sucipto, and Suzuki Pabelan. The source of data from the draft work documents in the industry is the RPS matkul in the automotive field of the PTM Study Program, vehicle inspection sheets, FGD minutes, and periodic service books for gasoline engines and diesel engines. The validity test technique used is data triangulation. Data analysis using content analysis techniques (Analysis content). First, the competencies that have been taught in the PTM Study Program, especially in the automotive field, have been in line with the competencies or jobs that exist in the industry. In the Focus Group Discussion process, the stake holders stated that the PTM Study Program curriculum is in line with the industry and provides input on curriculum development to pursue industrial technology that is always developing at all times in the form of electric car competencies and conventional competencies are only given at a glance and prioritize injection competencies.